Cyclic performance of fully assembled joints between H-Beam and CFST shear wall. (May 2023) - Liu, Yifeng; Cai, Honghao; Liu, Xiaoguang; Zhao, Junxian; Zhang, Chuntao
Abstract: The steel pipe of the concrete bundle shear wall is a new structural system suitable for steel structures. This study presents experimental findings of six fully assembled end-plate joints of H-beam based on high-strength bolts and one fully assembled side-plate joint of the concrete-filled steel tubes (CFST) shear wall. Two fully assembled joints of H-beam were proposed for the concrete bundle shear wall. Seven joints were subjected to low-cycle reciprocating tests in this testing program. The experimental parameters included the thickness of the end plate for H beam, the thickness of the end plate on wall, and the anchorage length of the bolts in the concrete, among which, the side-plate joints effectuated the rigid connection of unsupported frames in EC3 classification. Moreover, two fully assembled joints proposed in this study could effectuate the rigid connection of supported frames in EC3 classification. The strengthened end-plate joints significantly exceeded the rigid connection stiffness limit. The test results also indicated that the stiffness of the end-plate joint primarily depended on the thickness of the end plate for H beam and end plate on wall, while the side-plate joint mainly dissipated energy through the slip of bolts, which had excellent ductility and energy dissipation capacity, and thereby exhibiting the characteristics of low yielding load capacity and high ductility.